Políticas públicas: sustentabilidade financeira dos contratos administrativos - Oliveira, Antônio Flávio de (2019)
It was argued by some authors that sustainability corresponds to a principle and not only a criterion included in public procurement and contracting, it was understood for some time that this would only be an influx of the environmental question on the expenses that the Public Power would perform, without granting it a broader connotation, to cover aspects such as the existence of correspondence between economic means and the necessary expenditures. The vision of sustainability as a principle and not just as a criterion, leads to the need for public policies themselves to be designed by observing it. Therefore, from this perspective, it is necessary to adopt mechanisms that allow the sizing of public expenditures that stand out from bidding and contracting leading in a planned way, so that there is a correspondence between resources and needs that will be met. With the collection of data on works inspected by the Brazilian Court of Auditors, two interesting and equally relevant aspects for the control of public expenditures were found. The first one, which was not a research scope, was the difficulty of obtaining data that should be made available on transparency sites; while the second corroborated the hypothesis originally formulated that the lack of planning compromises the economic sustainability of public works and services, delaying them and increasing the final value. It ends with the presentation of recommendations that, adopted, may give greater sustainability to the administrative hirings.